SOCIAL STRUCTURES AND STEREOTYPES: CLASS AND RACE ALLEGORIES IN THE MAGICAL WORLD OF J.K. ROWLING - Jun , Li Wei; Ling, Zhang Xiao (International Research Journal of Arts and Communication, 2024)
The "Harry Potter" series, authored by J.K. Rowling, has garnered global acclaim as a prominent work of children's literature. However, its political allegorical aspects have often been overshadowed by its reputation as a piece of children's entertainment. This paper sheds light on the strong political allegorical elements woven into the narrative, characters, and overarching themes of the "Harry Potter" series, underscoring their resonance with deep-seated class and racial issues in British society. The allegorical potency of the series is notably exemplified in the portrayal of three distinct factions within the wizarding community. A meticulous examination of the text reveals a wealth of political and allegorical intricacies in "Harry Potter." This is vividly apparent in the racial tensions among wizards and the detailed exploration of characters' ethnic backgrounds. Furthermore, Rowling's adept use of symbolism throughout the series lends credence to the presence of political allegory, opening the door to meaningful analysis and interpretation.